Temporal Onset Focal Seizures Induced by Intermittent Photic Stimulation - Niu, Yue; Gong, Pan; Jiao, Xianru; Yang, Haipo; Yang, Zhixian (Frontiers in Neurology, 2021)
The study aimed to review the clinical, electroencephalogram (EEG), radiological, and pathological findings of pediatric epilepsy patients with temporal onset focal seizures induced by intermittent photic stimulation (IPS). Four patients with temporal onset photosensitivity focal seizures were analyzed. Three (75%) of four patients were female. The average age of seizure was 4.4 years. The interictal EEG showed both generalized and focal spike-and-wave in one patient, focal or multifocal spike-and-wave alone in three patients. Photoparoxysmal response (PPR) was evoked in all patients, and showed generalized discharges (patient 2-4), both generalized and posterior discharges (patient 1). Both generalized and focal discharges could coexist in interictal discharges and PPR. The sensitive frequencies of PPR and photo-convulsive response (PCR) were 12-30Hz and 10-16Hz, respectively, which were close to the occipital rhythm. Four patients were monitored the onset of PCR, namely the left anterior middle temporal lobe (TL), the left posterior TL, and the whole left TL, which showed two forms: one was the onset of slow waves in the temporal area without spreading generalized discharges (patient 1 and 4), and the other was fast rhythmic activities in the temporal area, spreading to the occipital area or gradually evolving into the generalized (patient 2 and 3). During follow-up, except for patient 3 who had occasional seizures, the rest of the patients were under control. Temporal onset focal seizures can be induced by IPS. Temporal onset photosensitivity seizures were mostly easy to control with antiseizure drugs.